DESIGN OF FRACTIONAL ORDER SLIDING MODE CONTROLLER FOR 2 DOF HELICOPTER SYSTEM - Kavuran, Gürkan; Yeroglu, Celaleddin (My University, 2018)
This paper presents a real time control application for a prototype helicopter system by using Sliding Mode Controlstrategy modified with small differential deviations. Experimental and simulation studies demonstrate theperformanceof the proposed controller for a class of flight systems with unstable dynamics. It is shown that theproposed controller decreases the steady state errors of the vertical and horizontal motion of the system. Smalldifferential deviations strengthen or weaken the effect of the differential to obtain better tracking response in case ofexternal disturbances. Numerical and experimental results match each otherto demonstratethe tracking of desiredrotor angles and suppression the disturbance effects.
Keywords: Robotik; Mühendislik; Hava ve Uzay